Attempting to Commit a Criminal Act: From the Perspective of Islamic Criminal Law - Khairunnisa Siregar; Diaz Albani; Muhammad Akbar Al Falah Amri; Nazwa Auliya Pratiwi (ISNU Sumatera Utara, 2024)
An attempted crime is an act that has been initiated by the perpetrator with the aim of committing a crime, but is not completed or does not produce the desired consequences due to certain obstacles. This study aims to analyze the concept of attempted crime from the perspective of Islamic criminal law through the views of four Islamic schools of thought, namely Imam Hanafi, Imam Maliki, Imam Syafi'i, and Imam Ahmad bin Hanbal, and examines the stages of implementation of the crime according to Al-Mawardi's thoughts in Ahkam al-Sulthaniyyah. This study uses a normative legal research method with a library research approach through analysis of the Qur'an, hadith, classical fiqh books, and Islamic criminal law literature. The results of the study indicate that the four schools of thought agree that hudud and qisas punishments can only be applied if all elements of the crime have been perfectly fulfilled. Meanwhile, attempted crimes that have not fulfilled these elements can still be subject to ta'zir sanctions based on the judge's discretion by considering the intention, actions, and level of danger posed. The stages of criminal conduct include intent, preparation, initiation of execution, completion of the crime, evidence gathering, and enforcement of the verdict. This concept demonstrates that Islamic criminal law prioritizes the principles of justice, prudence, and public welfare in law enforcement.